Technical Analysis of Kort Nozzle Application for SPOB Ship 4990 DWT on River - Tony Bambang Musriyadi; Amiadji; Bayu Sukma Cahyono (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2017)
Propeller is a locomotor shaped vanes are used to drive ships, and also propellers which serves to move tehaga by changing the turning force of the propeller thrust menggerakakan into the vessel. In increasing the value of the thrust to be generated that is by applying the kort nozzle propeller. The method used in this study using CFD (Computional Fluid Dynamic), and the variation is from the conventional propeller models, with a kort nozzle propeller type kort nozzle type 19A and 37. Based on the findings that the kort nozzle propeller with the addition of the value of the thrust , propeller efficiency and torque generated. The driving force value is by using kort nozzle propeller type 37 amounted to 349.27 kN.